2017
DOI: 10.1186/s13024-017-0160-5
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-type plasminogen activator exerts EGF-like chemokinetic effects on oligodendrocytes in white matter (re)myelination

Abstract: BackgroundThe ability of oligodendrocyte progenitor cells (OPCs) to give raise to myelin forming cells during developmental myelination, normal adult physiology and post-lesion remyelination in white matter depends on factors which govern their proliferation, migration and differentiation. Tissue plasminogen activator (tPA) is a serine protease expressed in the central nervous system (CNS), where it regulates cell fate. In particular, tPA has been reported to protect oligodendrocytes from apoptosis and to faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…tPA is naturally expressed in both gray and white matter, including within oligodendrocytes of the CC, but tPA expression in the CC declines with age, perhaps reducing the regeneration potential of white matter (35). After lysolecithin-induced white matter demyelination, endogenous tPA accelerates the migration of oligodendrocyte precursors to the lesion site through its EGFlike domain (36). Furthermore, endogenous tPA protects neurons against ischemic injury, and exogenous tPA mitigates white matter damage 24 h poststroke (17,18,35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…tPA is naturally expressed in both gray and white matter, including within oligodendrocytes of the CC, but tPA expression in the CC declines with age, perhaps reducing the regeneration potential of white matter (35). After lysolecithin-induced white matter demyelination, endogenous tPA accelerates the migration of oligodendrocyte precursors to the lesion site through its EGFlike domain (36). Furthermore, endogenous tPA protects neurons against ischemic injury, and exogenous tPA mitigates white matter damage 24 h poststroke (17,18,35).…”
Section: Discussionmentioning
confidence: 99%
“…Although tPA treatment has shown neuroprotective effects and promotes neurovascular remodeling or regeneration (17,18,27,(36)(37)(38), the use of tPA is not currently indicated in head trauma due to somewhat contradictory perceptions of an increased risk of brain hemorrhage and edema (42). Intravascular delivery of the free form, but not of erythrocyte-bound tPA, was reported to increase cortical tissue injury and hemorrhage after TBI (43).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it has been shown that tPA can act via non-proteolytic "growth factor-like" effects [30], some of them mediated by its EGF-like domain [4,14] The addition of the EGFR blocking agent AG1478 decreased MHC-II + expression on MHC-II + APCs as compared to the condition with tPA (DCs: 55.49% ±20.64; M : 77.76%±18.82; P < 0.001, Fig. 7C and D).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to its protease activity, tPA exerts various functions due to its ve distinct functional domains: nger domain, Epidermal Growth Factor (EGF)-like domain, kringle 1, kringle 2 and protease domain [13]. We have previously shown that tPA, by activating the EGF receptor (EGFR), has an anti-apoptotic effect over oligodendrocytes [4] and a chemotactic effect on their progenitors that helps remyelination after chemically-induced white matter lesions [14]. tPA is also able to increase blood brain barrier (BBB) permeability and helps leukocyte diapedesis [15] by several mechanisms, including the potentiation of endothelial N-Methyl-D-Aspartate receptors (NMDAR) [16] or tight junction disruption by the modi cation of occludin phosphorylation [17].…”
Section: Introductionmentioning
confidence: 99%
“…Mice lacking NG2 fail to expand their OPC population [113,114]. The epidermal growth factor (EGF) and vascular endothelial growth factor A (VEGFA) bind to their receptors on OPCs, EGFR, and VEGFR, respectively, and activate intracellular signaling, driving OPC migration [115][116][117][118]. Interestingly, there is a mutually beneficial relationship between OPCs and the vascular/perivascular population: OPCs regulate angiogenesis and pericyte colonization of the vasculature, while blood vessels and their associated cells support OPC proliferation, survival, and migration [97,104,117].…”
Section: Role Of Vascular and Perivascular Cells In Oligodendrogenesismentioning
confidence: 99%